Substantiation of the method for administration of Salsola collina dry extract into “Сo-trimoxazole” oral suspension - Глущенко, Алла Володимирівна; Георгіянц, Вікторія Акопівна; Ковалевська, Інна Вʼячеславівна; Рубан, Олена Анатоліївна (ScienceRise: Pharmaceutical Science, 2016)
Aim. Substantiation of the method for administration of Salsola collina dry extract into “Co-trimoxazole” oral suspension to avoid the negative effects of the drug on the hepatobiliary system. Considering the studied physical and chemical indicators of the herbal component, development of the new combined drug technology is planned. Methods. Dry extract of the aerial part of Salsola collina of the Chenopodiaceae family was used for research. The shape and size study of the suspension particles was carried out using monocular 4-objective Konus Academy (Italy) microscope with 360 o rotary monocular and 160 mm focal length equipped by ScopeTek DCM camera. ScopePhoto software was used for the images processing. Results. The shape and size of the Salsola collina dry extract particles was studied, its solubility depending on solvents and conditions was determined. Considering the studied physical and chemical constants, technological scheme of the new combined remedy was developed. Conclusion. On the basis of the study of physical and chemical properties of Salsola collina dry extract, technology of the new combined remedy was developed. It was determined, that the optimal way for dry extract administration into the suspension was its preliminary suspending in purified water at temperature of 60 °С with viscosity regulator consistent addition